THE EFFECT OF MIND MAPPING TECHNIQUE ON THE SECOND YEAR STUDENTS’ ABILITY IN WRITING DESCRIPTIVE PARAGRAPHS AT SMK YPPI TUALANG - Putri, Mentari Eka; Aruan, Rumiri; ', Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This pre-experimental research aimed to find out whether there is significant effect of Mind Mapping technique on the second year students’ ability in writing descriptive paragraphs at SMK YPPI Tualang. The writer used cluster sampling technique to determine the sample. The samples in this study were 30 students. Writing test is used to get the data on pre-test and post-test. In analyzing the data, the writer used t-test formula. The analysis of the data showed that there was significant effect of using Mind Mapping technique on students’ ability in writing descriptive paragraphs. The mean score of the students’ pre-test was 50.34. The mean score of the students’ post-test was 72.12. Moreover, from the statistical analysis, it was found out the t-obs (9.85) was higher that t-table at the level of significance 0.005 (1.699). Based on this finding, it is concluded that Mind Mapping technique can be used by the teacher as an alternative technique in teaching writing.Keywords: Mind Mapping Technique, Writing Ability, Descriptive Paragraph